Aggregation‐Induced Emission Luminogens for Gas Sensors - Yongbo Yu; Si‐Wei Zhang; Jinhui Jiang; Fulong Ma; Richard Wang; Tonghui Huang; Jianwei Zhao; Chao He; Guodan Wei (Advanced Sensor Research, 2023)
Abstract Luminescent chromophores armed with aggregation‐induced emission (AIE) characteristics can switch their fluorescence sensing by manipulating the aggregation and disaggregation states, leading to high sensitivity and high signal‐to‐noise ratio sensors. Accordingly, aggregation‐induced emission luminogens (AIEgens) have been widely applied to various biosensing, one of which is the gas sensors. Due to the weak signal, easy diffusion, difficult capture, and instability of gas molecules, electrochemical or infrared tests are generally used for detection. However, electrochemical tests have high power consumption, and the environment easily disturbs infrared tests. Fortunately, photochemical sensors utilizing AIE properties can effectively overcome these deficiencies. AIEgens usually exhibit large Stokes shift, good photostability, and low random blinking, suggesting excellent sensing reproducibility and many achievements have been obtained in AIEgens‐based gas sensors. This review summarizes the gas detection mechanism of AIEgens, and enumerate the reported gas sensors based on AIEgens. Then a perspective on the field and challenges facing it are elaborated so that researchers can better understand the development status of this field and develop more AIE‐type spectroscopic probes with gas‐responsive functions. It is expected to greatly enrich the types of gas sensors and promote the development of the application of AIE properties.